Pricing with Cookies: Behavior-Based Price Discrimination and Spatial Competition - Choe, Chongwoo; King, Stephen; Matsushima, Noriaki (Management Science, 2018)
We present a model of dynamic competition between two firms where firms gather customer information through first-period purchase. This creates asymmetric information in the second period whereby a firm knows more about its own past customers than its competitor does. We examine how the ability to offer personalized prices based on customer information affects prices and profit over the two periods. When product differentiation is exogenously fixed, asymmetric information leads to two asymmetric equilibria where one firm chooses more aggressive pricing to secure a larger first-period market share. When product differentiation is also chosen endogenously, there continue to exist two asymmetric equilibria where one firm chooses more aggressive positioning. The more aggressive firm, whether through pricing or positioning, can force the game to be played to its advantage. But both firms end up worse off compared to when they use simpler pricing strategies or commit to substantial product differentiation. The online appendix is available at https://doi.org/10.1287/mnsc.2017.2873 . This paper was accepted by Juanjuan Zhang, marketing.